The weighting approach according to Sheikh Muhammad bin Badi Al-Kanti Al-Jaza’iri through his book “Fath Al-Mu’ttaal” - neche, walid; hammadi, abdelfetah (Journal of Social Sciences and Humanities, 2024)
Weighting is considered one of the original fundamentalist chapters, and an indispensable art for fundamentalists, the result of the controversial issues and the purpose of presenting them, what is highlighted the eligibility for consideration and ijtihad or not. Every scholar has his own way and approach in presenting what he deems most likely, in this study, i wanted to get acquainted with the approach of one of the famous figures of our beloved country - Algeria - the obscure "Muhammad bin Badi" through his buried fundamentalist book "Fath al-Muttaal", first I discussed the definition of the author and the book, and then defined the weighting. Then, I discussed his approach through an inductive study of his book, which identified the most important features of his method and approach in weighting, to show his distance from tradition, his independence in his opinion, his practice, and the height of his ability.